Analisis Dampak Potongan Harga terhadap Minat Beli Konsumen Kazana Kosmetik di Medan Perjuangan - Revita Sari; Dinda Tri Jelita (Kajian Ekonomi dan Akuntansi Terapan, 2024)
The aim of the research is to determine the impact of discounts on customer interest in Kazana cosmetics MSMEs in the field of struggle. The hypothesis in the research is that discounts have a positive impact on consumer interest. The type of research used is descriptive research. By using primary and secondary data sources. The data was analyzed using descriptive analysis data and qualitative analysis. The research results found that from this analysis price has a positive or significant influence on buying interest. The existence of price discounts will increase consumer buying interest, meaning that if the price discount is higher it will influence the high tendency of consumers to be interested in making purchases.